Effects of musical valence on the cognitive processing of lyrics. (November 2016) - Fiveash, Anna; Luck, Geoff
The effects of music on the brain have been extensively researched, and numerous connections have been found between music and language, music and emotion, and music and cognitive processing. Despite this work, these three research areas have never before been drawn together into a single research paradigm. This is significant as their combination could lead to valuable insights into the effects of musical valence on the cognitive processing of lyrics. This research draws on theories of cognitive processing suggesting that negative moods facilitate systematic and detail-oriented processing, while positive moods facilitate heuristic-based processing. The current study ( n = 56) used an error detection paradigm and found that significantly more error words were detected when paired with negatively valenced sad music compared to positively valenced happy music. Such a result explains previous findings that sad and happy lyrics have differential effects on emotion induction, and suggests this is due to sad lyrics being processed at deeper semantic levels. This study provides a framework in which to understand the interaction of lyrics and music with emotion induction – a primary reason for listening to music.